Tax and Benefit Reforms in a Model of Labour Market Transitions - Michał Myck; Howard Reed (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
We present a method for taking advantage of labour market transitions to identify effects of financial incentives on employment decisions. The framework we use is very flexible and by imposing few theoretical assumptions allows extending the modelled sample relative to structural models. We take advantage of this flexibility to include disabled people in the model and to analyse behaviour of disabled and non-disabled people jointly. A great deal of attention is paid to appropriate modelling of financial incentives on the labour market. This in the case of disabled people turns out to be an extremely complex process but one which in the end turns out well worth the effort. The model is used to compare reactions on the labour market to marginal changes in financial incentives and also to model one of the most important reforms of the UK Labour government, the introduction of the Working Families? Tax Credit. The methodology relies on matching transitions and incomes data between cross-sectional and panel surveys, and could be used in other countries where detailed reliable income data are not collected in a panel format.
Keywords: 330; Steuerreform; Sozialreform; Beschäftigungseffekt; Ökonomischer Anreiz; Behinderte; Großbritannien